2010
DOI: 10.1002/etep.420
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of internal temperature in stator winding of three-phase induction motors with ann

Abstract: This paper implements an artificial neural network (ANN) model able to estimate the internal temperatures in stator winding of a squirrel-cage three-phase induction motor fed by a voltage inverter. A sinusoidal pulse-width modulation (SPWM) inverter feeding three-phase induction motors were tested up to over load. The temperatures are measured in a node of stator winding. The results show that the ANN model produces reliable estimates of interior temperature of stator winding. Through this model, it is possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…7 for learning step. These coefficient shows that target and ANN output values were very related each other [18]. Also in Table 4, performance of the ANN system is illustrated.…”
Section: Testing the Networkmentioning
confidence: 95%
See 1 more Smart Citation
“…7 for learning step. These coefficient shows that target and ANN output values were very related each other [18]. Also in Table 4, performance of the ANN system is illustrated.…”
Section: Testing the Networkmentioning
confidence: 95%
“…Output summary of data set. showed that the optimal number of neurons in the hidden layer can be chosen as 35 also, the activation function has been chosen as a hyperbolic tangent sigmoid function for all of the layers [18].…”
Section: Selecting the Ann Architecturementioning
confidence: 99%
“…In this section investigative studies are conducted on the performance of the split air conditioner under distinct operational conditions, each of which reflecting the type of disturbance typically manifest, under the terms foreseen in current legislation and which regulates the question of energy quality indicators [22,23]. As usual, the studies include, for the same condition for the voltage supply, to obtain information to correlate and validate the results derived from the simulations with their counterparts extracted from laboratory tests.…”
Section: Performance Testsmentioning
confidence: 99%
“…Therefore, in the process of the motor design, the temperature limits should be calculated and checked for satisfying the requirements of functionality and safe. If the operating temperature exceeds the insulation material working limit of the motor [1], it will cause an accelerated aging effect or even failure of insulation [2,3], and then machine life expectance can be seriously affected [4]. Accordingly, it is vital to plot the thermal map of the electric machine, working in the most severe condition.…”
Section: Introductionmentioning
confidence: 99%